Setting priorities for regional conservation planning in the Mediterranean Sea. - Fiorenza Micheli; Noam Levin; Sylvaine Giakoumi; Stelios Katsanevakis; Ameer Abdulla; Marta Coll; Simonetta Fraschetti; Salit Kark; Drosos Koutsoubas; Peter Mackelworth; Luigi Maiorano; Hugh P Possingham (PLoS ONE, 2013)
Spatial prioritization in conservation is required to direct limited resources to where actions are most urgently needed and most likely to produce effective conservation outcomes. In an effort to advance the protection of a highly threatened hotspot of marine biodiversity, the Mediterranean Sea, multiple spatial conservation plans have been developed in recent years. Here, we review and integrate these different plans with the goal of identifying priority conservation areas that represent the current consensus among the different initiatives. A review of six existing and twelve proposed conservation initiatives highlights gaps in conservation and management planning, particularly within the southern and eastern regions of the Mediterranean and for offshore and deep sea habitats. The eighteen initiatives vary substantially in their extent (covering 0.1-58.5% of the Mediterranean Sea) and in the location of additional proposed conservation and management areas. Differences in the criteria, approaches and data used explain such variation. Despite the diversity among proposals, our analyses identified ten areas, encompassing 10% of the Mediterranean Sea, that are consistently identified among the existing proposals, with an additional 10% selected by at least five proposals. These areas represent top priorities for immediate conservation action. Despite the plethora of initiatives, major challenges face Mediterranean biodiversity and conservation. These include the need for spatial prioritization within a comprehensive framework for regional conservation planning, the acquisition of additional information from data-poor areas, species or habitats, and addressing the challenges of establishing transboundary governance and collaboration in socially, culturally and politically complex conditions. Collective prioritised action, not new conservation plans, is needed for the north, western, and high seas of the Mediterranean, while developing initial information-based plans for the south and eastern Mediterranean is an urgent requirement for true regional conservation planning.